2009
DOI: 10.1007/s00595-008-3877-5
|View full text |Cite
|
Sign up to set email alerts
|

Two-port laparoscopic placement of a peritoneal dialysis catheter with abdominal wall fixation

Abstract: We devised a new laparoscopic technique for peritoneal dialysis catheter (PDC) placement to overcome the common problem of malfunction or migration of the catheter. Between March 2005 and August 2006, 38 patients underwent laparoscopic catheter placement with lower abdominal wall fixation. Using an abdominal scout film, we checked for catheter tip migration regularly. There was no leak in the immediate postoperative period. After follow-up of 21.5 months (range 6-34), all catheters were working properly, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…There are other reports of laparoscopic PD catheter placement describing excellent results. Ko J et al reported [30] that the success rate of laparoscopic PD-catheter was 100%. Other researchers have used stitches to fix the catheter in place during laparoscopy, with reported success rates of 94 to 100% [27,31].…”
Section: Discussionmentioning
confidence: 99%
“…There are other reports of laparoscopic PD catheter placement describing excellent results. Ko J et al reported [30] that the success rate of laparoscopic PD-catheter was 100%. Other researchers have used stitches to fix the catheter in place during laparoscopy, with reported success rates of 94 to 100% [27,31].…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have showed that a low incidence of catheter malfunction can be achieved by creating a short, mobilizable intra-abdominal catheter (30,(40)(41)(42)(43)(44). It is reasonable that the short length of the intra-abdominal segment may increase the nondeformability of the catheter tip and thus antagonize tip migration.…”
Section: Mechanical Complicationsmentioning
confidence: 99%
“…reported [33] that the success rate of laparoscopic PD-catheter was 100%. Other researchers have used stitches to fix the catheter in place during laparoscopy, with reported success rates of 94% to 100% [7,34] .…”
Section: Discussionmentioning
confidence: 98%